Water moon eaudiobook A novel. - Sotto Yambao, Samantha (Books on Tape, 2025)
A woman inherits a pawnshop where you can sell your regrets, and then embarks on a magical quest when a charming young physicist wanders into the shop, in this dreamlike fantasy novel. “Race through a lush world of pure wonder and romance—kites made of wishes that become stars, origami that holds time in its folds, and a night market in the clouds—in this lovely, cozy fantasy reminiscent of Erin Morgenstern's The Starless Sea .”— Booklist (starred review) On a backstreet in Tokyo lies a pawnshop, but not everyone can find it. Most will see a cozy ramen restaurant. And only the chosen ones—those who are lost—will find a place to pawn their life choices and deepest regrets. Hana Ishikawa wakes on her first morning as the pawnshop’s new owner to find it ransacked, the shop’s most precious acquisition stolen, and her father missing. And then into the shop stumbles a charming stranger, quite unlike its other customers, for he offers help instead of seeking it. Together, they must journey through a mystical world to find Hana’s father and the stolen choice—by way of rain puddles, rides on paper cranes, the bridge between midnight and morning, and a night market in the clouds. But as they get closer to the truth, Hana must reveal a secret of her own—and risk making a choice that she will never be able to take back. “Highly recommended . . . Readers who have been swept up in the cozy charm of Before the Coffee Gets Cold by Toshikazu Kawaguchi and The Dallergut Dream Department Store by Miye Lee will fall hard for the mix of magical realism, fantasy mystery, and star-crossed romance.”— Library Journal (starred review)